2021
DOI: 10.1182/blood-2021-146598
|View full text |Cite
|
Sign up to set email alerts
|

The Comparison of Kte-X19 to Current Standards of Care: A Pre-Specified Synthetic Control Study Utilizing Individual Patient Level Data from Historic Clinical Trials (SCHOLAR-3)

Abstract: Background: The ZUMA-3 trial of KTE-X19 in relapsed/refractory (r/r) adult B-cell precursor acute lymphoblastic leukaemia (B-ALL) utilizes a single arm design. To contextualize these results, a synthetic control (SC) study derived from individual patient-level data (IPD) sampled from historical clinical trials (CTs) was constructed. Aims: To compare the overall survival (OS) and objective complete response rate at week 24 (OCR24) results of the ZUMA-3 pivitol study using a matched (SC) derived f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…Detailed methodology of the retrospective cohort study SCHOLAR-3 was previously reported (Additional file 1 : Supplemental Methods) [ 8 ]. Briefly, propensity scoring was used to match adult patients with R/R B‑ALL treated in historical clinical trials (synthetic control arm [SCA]) with ZUMA-3-treated patients based on key baseline characteristics and prior therapies.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Detailed methodology of the retrospective cohort study SCHOLAR-3 was previously reported (Additional file 1 : Supplemental Methods) [ 8 ]. Briefly, propensity scoring was used to match adult patients with R/R B‑ALL treated in historical clinical trials (synthetic control arm [SCA]) with ZUMA-3-treated patients based on key baseline characteristics and prior therapies.…”
Section: Methodsmentioning
confidence: 99%
“…To better assess the unmet need for patients with R/R B-ALL and to estimate the benefit of KTE-X19 compared with standard-of-care regimens in this setting, we recently performed the retrospective, external historical control study SCHOLAR-3 [ 8 ]. Outcome comparisons were made based on matched individual patient-level data from historical clinical trials with ZUMA-3 patients [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Arm A scenario analysis was performed to compare outcomes of patients treated with KTE-X19 to IPD sampled from historical clinical trials of patients who had not previously failed blinatumomab. A post hoc analysis of the SCHOLAR-3 study was done using a synthetic control matching patients from ZUMA-3 (irrespective of pre-treatment with BLIN or INO) to BLIN-or INO-naı ¨ve patients from historical clinical trials (synthetic control arm 3 [SCA-3]) [27]. As patients in SCA-3 could have received either BLIN (92.5%) or standard of care chemotherapy (7.5%), the study population was further restricted to only reflect patients who received BLIN in the SCA-3 arm.…”
Section: Scenario Analysis With Synthetic Controlmentioning
confidence: 99%